Exploring the quality of life and its related factors among the elderly - Gunawan, Indra; Lin, Mei-Hsiang; Hsu, Hsiu-Chin (University of Muhammadiyah Semarang, 2020)
As the rapidly growing population of elderly people in the world that means they would be facing all challenges to their quality of life. As age increases, quality of life is often reported to decline. They are also at risk of mental illness, neurological disorder and more health problems affecting their quality of life. Depression is a common mental disorder among the elderly. The objective of this study is to understand the relationship between depression and quality of life among the elderly in an Indonesian nursing home. This research use the descriptive correlational and cross-sectional design was applied. There were 114 elderly recruited by convenient sampling. The results of this study showed the mean age of the elderly was 71.2 at the time of data collection ranging from 65 to 76 years old. The variables associated with quality of life were age, gender, education, marital status, ethnicity, chronic disease, and depression status. Moreover, the study found that, as predictors, the variables that influenced the quality of life according to relevance were: age, depression status, and educational level. Age and depression status is recognized as significant predictors of the quality of life among the elderly in an Indonesian nursing home. The result of the study would serve as references to the future and related promotion for the same field of the study